Small-scale spatial variation of meiofaunal communities in Lima estuary (NW Portugal) assessed through metabarcoding - Fais, Maria (2020)
Meiofaunal organisms play a key role in estuarine ecosystems, being responsible for significant ecological processes. However, meiofauna constitutes a particularly difficult community to be monitored through conventional morphology-based approaches. New emerging tools, such as DNA metabarcoding, facilitate the access to these communities and provide an opportunity to develop routine monitoring programs. In the present study, the small-scale spatial variation of meiofaunal communities in the Lima estuary (NW Portugal) was investigated using DNA metabarcoding. The first stage of the study aimed to establish the amount of sediment sample to be used for DNA extraction and to test six primer pairs, three of them amplifying fragments from the mitochondrial cytochrome c oxidase gene (COI) and three other the nuclear ribosomal 18S rRNA gene (18S). In a subsequent stage, sediment samples were collected in four stations along an estuarine gradient (salinity ranging between 9 and 28), in which six sampling points about 4–5 m apart were considered: three in the high intertidal and three in the mid intertidal. After the DNA extraction from sediments, COI and 18S amplicon libraries were produced and sequenced in an Illumina MiSeq platform. OTUs (operational taxonomic units) recovered by either COI or 18S displayed generally high turnover in occurrence among sampling points within a station and tidal horizon, among tidal horizons within a station, and among stations of distinct salinity (approx. 60–93%). Both markers recorded little variation among stations in OTU richness and in the taxonomic composition of the most dominant groups. However, the meiofauna detected differed qualitatively between the two markers used; Amoebozoa and Cnidaria were mostly detected with COI while Ciliophora and Platyhelminthes with 18S. In addition, the structure of the meiofauna community diverged significantly among stations and was strongly influenced by salinity and sediment features. Globally, results indicated a highly patchy distribution of meiofauna taxa in the Lima estuary, revealed by the high OTU turnover even between sampling points only a few meters apart. Hence, eDNA-based meiofauna surveys require consideration of the necessary sampling effort on relatively small spatial scales, as well as an appreciation of the tidal level-induced variation of these communities.